Analisis Penentuan Harga Pokok Produksi Pada Usaha Bakso Babi Ujung Pandang Di Rantelemo Kabupaten Tana Toraja - Asriani Ari Paembonan; Agustinus Mantong; Grace Sriati Mengga (Jurnal Penelitian Multidisiplin, 2023)
Asriani Ari Paembonan (2023). This study aims to determine the cost of production in the business of pork meatballs in Ujung Pandang in Rantelemo, Tana Toraja Regency. This study uses the financial reports of the pork meatball business from the point of view. The sample in this study is the business of pork meatballs at the tip of the view. The data analysis technique used to calculate the cost of production uses full costing. The result of the research is the Ujung Pandang Pork Meatballs in calculating the cost of production is still using a simple method. The calculated costs still do not include all costs incurred. The results of the calculation of the cost of production according to the company's estimates will get a profit when in fact if it is calculated using the full costing method the company will not get a profit because the value of the calculation of the full costing method is the cost of production which is Rp. 607,686. Determination of product selling prices based on cost of sales using the cost plus pricing method with the desired profit of 5%